Action Learning To Improve Students' Green Leadership Abilities - Khusnul Hotimah; Alen William Fredrick; Harnida Wahyuni Adda; Risnawati Risnawati; Wiri Wirastuti (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The challenges of environmental degradation and global climate change demand a transformation of leadership paradigms in higher education institutions, particularly in management education. This study aims to analyze the influence of student involvement in the Green Leadership in Action program—an Action Learning-based initiative—on the development of sustainable leadership competencies in the Undergraduate Management Study Program at Tadulako University. Methods: This study used a descriptive and inferential quantitative approach, involving 50 students as respondents through a purposive sampling technique. The research instrument was a closed-ended questionnaire measuring five competency dimensions: green vision, sustainable innovation, cross-team collaboration, social responsibility, and environmental ethics. Results: The results of data analysis using the Pearson correlation test showed a strong positive relationship between student involvement and Green Leadership competencies (r = 0.77). Furthermore, a simple linear regression test confirmed the significant influence of the Action Learning variable on the formation of green leadership (F = 72.696; p < 0.001). Descriptively, the cross-team collaboration dimension recorded the highest achievement, while the team reflection and environmental ethics indicators scored the lowest. Implication: These findings provide academic legitimacy that action-based learning is effective in internalizing sustainability values, but institutions need to strengthen the structure of reflection and the moral-affective dimension to balance physical action with wisdom.